Elucidating Collapse-Resistant Mechanisms of Pore Geometries in Fire Ant Nest Cavities - Tyler Felgenhauer; Satchi Venkataraman; Ethan Mullen (Biomimetics)
Porous materials and structures, such as subterranean fire ant nests, are abundant in nature. It is hypothesized that these structures likely have evolved biological adaptations that enhance their collapse resistance. This research aims to elucidate the collapse-resistant mechanisms of pore geometries in fire ant nests. Finite Element Models of ant nests in soil were generated using X-ray CT imaging of aluminum castings of ant nests. Representative volume elements of the ant nests, representing porous structures at various depths, were analyzed under confined compression. This work on investigating fire ant (sp. Solenopsis Invicta) nests found them to be hierarchical and graded at various depths that affect how they resist loads and collapse. The top portion acts as a protective shield by distributing damage and absorbing energy. In contrast, the lower chambers localize stress, contributing to damage tolerance. This research provides evidence to suggest that ant nests have developed properties that allow them to resist collapse. These findings could inform the design of lightweight and durable cellular structures in various engineering fields.